A computational study of magnesium incorporation in the bulk and surfaces of hydroxyapatite - Almora-Barrios, Neyvis (Langmuir : the ACS journal of surfaces and colloids, 2013)
We have used a combination of static lattice energy minimization and molecular dynamics simulations to investigate the thermodynamics of Mg incorporation into the bulk and hydrated surfaces of hydroxyapatite (HA). In agreement with recent experimental and theoretical work, our simulations show that the incorporation of low levels of Mg in the Ca (II) site is preferred with respect to incorporation in Ca (I) sites. However, we predict that Mg in the HA bulk material is metastable both with respect to the Mg/Ca exchange with aqueous solution and with respect to separation into bulk phases of magnesium phosphate [Mg3(PO4)2] and magnesium hydroxide [Mg(OH)2]. This finding suggests that Mg siting in the HA bulk is at least partially controlled by kinetics rather than by thermodynamics during crystal growth, which can explain the discrepancies found in the literature about the preferential substitution site. Finally, we found that Mg incorporation from solution into the hydrated surfaces, rather than the bulk material, is energetically favorable, in particular in the (011̅0) plane where cation sites are exposed to solution, thereby enabling the favorable interaction of Mg with water